KONSTRUKSI UTANG-PIUTANG (QARDH) DAN PENGGUNAANNYA PADA BANK SYARIAH DI INDONESIA (PENDEKATAN TAFSIR AYAT AHKAM) - Tri Hidayati; Muhammad Syarif Hidayatullah (Al-Mizan (e-Journal), 2022)
This paper aims to explain the content of qur'anic verses related to debts (qardh) with the interpretation of law verses in the Quran approach and seeks to study the construction of debt contracts and their application to Islamic banking products in Indonesia. The research method used is normative legal research with a conceptual approach, namely the concept of debt that is the focus of the study. The commentator of Quran (mufassir) such as Ibn Kathir, Ibn 'Arabi, Hamka, and M. Quraish Shihab explained that the verses about al-qardh motivate humans through the hyperbole “lend to Allah” to sacrifice some of his wealth by lending to others who are in dire need without expecting anything (tabarru' or tatawwu'). The use of debt in the operation of Islamic banks is in the distribution of bailout funds and qardhul hasan financing products (virtue loans) which are manifestations of the distribution of social funds.